2015
DOI: 10.1016/j.mad.2015.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Metformin inhibits age-related centrosome amplification in Drosophila midgut stem cells through AKT/TOR pathway

Abstract: We delineated the mechanism regulating the inhibition of centrosome amplification by metformin in Drosophila intestinal stem cells (ISCs). Age-related changes in tissue-resident stem cells may be closely associated with tissue aging and age-related diseases, such as cancer. Centrosome amplification is a hallmark of cancers. Our recent work showed that Drosophila ISCs are an excellent model for stem cell studies evaluating age-related increase in centrosome amplification. Here, we showed that metformin, a recog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 77 publications
3
16
0
Order By: Relevance
“…3-3-6) support the findings that AKT [23] and ROS [17] can mediate centrosome amplification, and further place AKT upstream of ROS. In an apoptosis model, activation of ROCK1 causes AKT inactivation [24], which is different from our results that placed ROCK1 downstream of AKT activation (Figs.…”
Section: Discussionsupporting
confidence: 64%
“…3-3-6) support the findings that AKT [23] and ROS [17] can mediate centrosome amplification, and further place AKT upstream of ROS. In an apoptosis model, activation of ROCK1 causes AKT inactivation [24], which is different from our results that placed ROCK1 downstream of AKT activation (Figs.…”
Section: Discussionsupporting
confidence: 64%
“…Our results (Figs. 3-6) support the findings that AKT (Na et al, 2015) and ROS (Chae et al, 2005) can mediate centrosome amplification, and further place AKT upstream of ROS. In an apoptosis model, activation of ROCK1 causes AKT inactivation (Zhang et al, 2016), which is different from our results that placed ROCK1 downstream of AKT activation (Figs.…”
Section: Discussionsupporting
confidence: 57%
“…35 Fourth, metformin inhibits the AKT/TOR signalling pathway to inhibit age-and oxidative stress-induced centrosome amplification. 36 Here we found that the improvements in cardiac remodelling caused by metformin upon β-AR over-activation in the old mice are due to AMPK activation and a decrease in β-arrestin 1 expression ( Fig. 5).…”
Section: Discussionmentioning
confidence: 64%